Revisie in vertaling: wanneer en wat - Breedveld, Hella; van den Bergh, Huub (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Translators often go through their texts several times before considering their translations ‘done’. In most translation process research the different runs through the text after producing a draft version of the translation are considered as a single revision stage of the translation process. If, however, the factor time is taken into account, it might be expected that the revision activities a translator performs differ in nature and function depending on the moment where they occur during the translation process. The present article is a search for describing and understanding revision processes based on this view. Revision activities in the think-aloud protocols of five translators are analysed with regard to cognitive context and text processing characteristics. Results show that there is little evidence that revision activities vary during the translation process. Revision activities seem to occur at random throughout the translation process and appear to be triggered locally.